2020
DOI: 10.9734/ijtdh/2020/v41i230250
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance and Healthcare Quality: A Comparative Study between Insured and Uninsured Patients at a Teaching Hospital in Northeast Nigeria

Abstract: Objective: Patients’ perception of the quality of care is essential in assessing health services and feedbacks from patient satisfaction surveys are useful in healthcare quality improvements. Methods: A descriptive cross-sectional study was done to evaluate satisfaction with the quality of care among insured patients under the National Health Insurance Scheme (NHIS) and uninsured (Out-of-Pocket paying) patients at University of Maiduguri Teaching Hospital (UMTH), Maiduguri, Borno State, Nigeria. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
3
4
1
Order By: Relevance
“…The findings of this study show that overall patient satisfaction with healthcare services was 65.6%. The findings of this study are in harmony with studies done in Arsi, Ethiopia (63.4%) (31), northcentral Nigeria (63.1%) (32), and southeastern Nigeria (68.8%) (25). However, the findings of this study were higher than those of studies conducted in Nigeria (58.1%) (25), Ethiopia (54.7%) and (54.1%) (33,34), Turkey (53.3%) (35), Ghana (43%) (36), and southern Nigeria (40%) (37).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The findings of this study show that overall patient satisfaction with healthcare services was 65.6%. The findings of this study are in harmony with studies done in Arsi, Ethiopia (63.4%) (31), northcentral Nigeria (63.1%) (32), and southeastern Nigeria (68.8%) (25). However, the findings of this study were higher than those of studies conducted in Nigeria (58.1%) (25), Ethiopia (54.7%) and (54.1%) (33,34), Turkey (53.3%) (35), Ghana (43%) (36), and southern Nigeria (40%) (37).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings also revealed that the satisfaction level among insured patients was 68.8%, while it was 62.4% among uninsured patients. This finding is lower than studies conducted in Northern Nigeria ( 25 ), Nepal (83.2% insured and uninsured patients, 84.8%) ( 38 ), Tanzania (71% insured and 81% uninsured patients) ( 28 ), North East Nigeria (76.5% insured patients and 68.7% uninsured patients) ( 25 ), and Ethiopia (79.4% insured and 75.7% uninsured patients) ( 39 ). The variation in sample size, socioeconomic level, and study design could all be contributing factors to the reason.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Plausible reasons adduced for this were better workflow, fewer workloads, and stricter third-party supervision in the NHIS clinic. The obverse report of uninsured patients being more satisfied with the quality of care ( 28 ) and time spent was adduced to the cash-backed nature of the dealings with providers who are incentivized by tokens from patients who are in turn, readily given prompt and better attention by health workers ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%